Superficial tinea infections of the genital region in women - Rotsztejn, Helena; Zalewska, Anna (Menopause Review/Przegląd Menopauzalny, 2005)
The aim of the study was to present a concise overview based on clinical presentations, diagnostic possibilities and treatment of mycotic infections most commonly encountered in women in the anogenital region.